Pharmacist-Led Medication Reconciliation: Impact on Patient Safety and Healthcare Outcomes - Sami Mohammed S. Alsheheri; Mazen Saleh Mohammed Altawyan; Bashayer Mohammad Alshehri (International Journal of Medical Toxicology and Legal Medicine, 2024)
Pharmacist-led medication reconciliation is a vital process that ensures the accuracy of patient medication information, especially during transitions of care. This review examines the role of pharmacists in medication reconciliation, focusing on their impact on reducing medication errors, preventing adverse drug events (ADEs), and improving overall patient safety in various healthcare settings. The evidence suggests that pharmacist interventions significantly contribute to improved healthcare outcomes by mitigating risks associated with medication discrepancies. Pharmacists’ expertise in drug therapy, their ability to identify discrepancies, and their direct involvement in patient care position them as integral members of the healthcare team, particularly during critical transitions such as hospital admissions, transfers, and discharges. By enhancing medication safety, pharmacist-led reconciliation improves clinical outcomes and reduces healthcare costs.